ISOLATION AND CHARACTERIZATION OF AMYLASE-PRODUCING MICROBES FROM THE DIGESTIVE TRACT OF TILAPIA - Sri Wahyuni; Teguh Satria Amin; Nomi Noviani; Leni Handayani (Jurnal Ilmiah Teunuleh, 2021)
Enzymes are natural products that play an important role in various industrial applications, from food processing to chemical products. One of the most widely used enzymes is amylase. Amylase is an enzyme that plays a role in starch hydrolysis. Amylolytic bacteria can be isolated in the digestive tract of fish. This is most bacteria that occupy the digestive tract have high activity. This study aims to obtain a potential isolate producing amylase bacteria whose activity can be determined through morphological characterization and activity test of enzyme-producing bacteria. The results obtained from this study were ten isolates with the potential to produce amylase enzymes, which were marked with a positive test after the addition of iodine.